THE INFORMATIONAL-PSYCHOLOGICAL INFLUENCE DURING THE ARMED STRUGGLE - Aleshchenko, V. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2019)
The article highlights the essence of the concept and general trends in the implementation of the information-psychological influence in the course of armed struggle. Informational and psychological component in military affairs that dominates in countries such as the United States, Germany , Great Britain, France, China, Russia and the main tasks assigned to the special forces information (force) are considered. Some priority areas to counter the information-psychological influence in the course of armed struggle are proposed.
Keywords: the information-psychological influence, informational and psychological confrontation, information and psychological operations, informational-psychological action, informational-psychological activities